Monitoring of Social Vulnerability Website Base in Central Java Province - Widiyanto, Widiyanto; Anam, Khaerul; Wiradharma, Gunawan; Nurdiansyah, Aulia (Komunitas, 2021)
The state must maintain the security of its territory. Regional conduciveness has a significant influence on improving the welfare of its people. A region, both central and regional, cannot be separated from conflict and social security. Kesbangpol is an institution tasked with maintaining conduciveness and early awareness of vulnerabilities in national unity, politics, community, social and cultural protection. In carrying out this task, Kesbangpol collects data from the field and then processes it and reports it to the government for review in maintaining regional conduciveness. The data collection process to the reporting process is still inefficient. Therefore, an information system is needed to collect, process data, and report information. An important function in the use of this information system is also expected to be able to map the current conflict so that the system can provide alternative solutions in handling these conflicts quickly and efficiently. Conflict maps are expected to visually describe conflict patterns from the data that has been obtained to facilitate and speed up the implementation of follow-up to the problems that are happening. In addition, with the application of artificial intelligence or a decision support system to the system, it is expected to be able to analyze the data so that it can take into account the warranties that will occur in the area and preventive measures can be taken so that conflicts do not happen.